MENINGKATKAN KEMAMPUAN OPERASI BILANGAN MELALUI PENGGUNAAN MEDIA MANIPULATIF - Eneng Sri Susilawati; Usmaedi Usmaedi (Universitas Setia Budhi Rangkasbitung, 2018)
This research was aimed at increasing basic mathematics ability in numeral operation aspect of students level B at Sejahtera I Kindergarten in Panggarangan using manipulative media. It was carried out in April to May 2017. Action research of Kemmis and Taggart (tahun) was used as the method of the research. It applied two cycles with 12 meetings. The cycles consisted of planning, acting, observing, and reflecting. The subject of the research were 13 kindergarten level B students of Sejahtera I Panggarangan. The data gained were assessment results of pre-cycle, cycle I and cycle II, fieldnote, interview, and documentation. Emills standard was used to analyze the data percentage, that the average increase of basic mathematics ability in numeral operation aspect reached 71%. The result of the research showed that there was an increase in basic mathematics ability using manipulative media. It was proven by the increase of the students' average assessment results. In cycle I the students' average score was 27,7, in cycle II it was 32,2. It means that there was an increase of 4,5 in the average score, from 76,9% in cycle I to 89,5% in cycle II. The implication of this study indicated that the use of manipulative media to teach basic mathematics in numeral operation brought about good result. In the learning process, the students became more active and creative. They found it easier to learning some mathematics concepts. In teaching mathematics concepts, manipulative media helped ease the teacher in explaining the concepts.